Nondestructive Testing (NDT) - Lacidogna, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The aim of this book is to collect the newest contributions by eminent authors in the field of NDT-SHM, both at the material and structure scale. It therefore provides novel insight at experimental and numerical levels on the application of NDT to a wide variety of materials (concrete, steel, masonry, composites, etc.) in the field of Civil Engineering and Architecture.